Research on the Occurrence State of Methane Molecules in Postmature Marine shales—A Case Analysis of the Lower Silurian Longmaxi Formation Shales of the Upper Yangtze Region in Southern China - Zhang, Kun; Song, Yan; Jiang, Zhenxue; Yuan, Xuejiao; Wang, Xueying; Han, Fengli; Zhang, Liwen; Tang, Liangyi; Liu, Pei; Yang, Yiming; Zeng, Yao; Chen, Xuecheng; et al. (Frontiers in Earth Science, 2022)
The Yangtze region in Southern China is endowed with abundant marine shale gas. Methane molecules exist in either adsorption state or free state in post-mature marine shales, depending on the components of shales. In this study, the core samples of the selected well in the Lower Silurian Longmaxi Fm. shales from the Sichuan Basin, upper Yangtze region, Southern China were taken as study objects. We carried out TOC content, organic-matter maturity, mineral components, core gas content analyses, and isothermal adsorption, FIB-SEM, and FIB-HIM experiments to analyze the occrence state of methane molecules in post-mature marine shales. The conclusions are as follows: most methane molecules exist in the organic-matter pores of the post-mature marine shales and only a small amount of them in clay mineral pores. The organic-matter pores in organic-rich shales are large in number with excellent roundness and are well-connected, with large pores covering small ones. Thus, abundant free gas can be stored in the organic-matter pores and pore throats, making it possible to densely and continuously adsorb methane molecules with a relatively large adsorption space. The flake-shaped clay minerals have a small number of pores with low roundness. Among the three clay minerals in post-mature marine shales of the Longmaxi Fm., I/S mixed layer offers certain reservoir spaces for adsorbed and free gas, Chlorite stores a little adsorbed gas and little free gas, while illite hardly stores the adsorbed gas but contains a little free gas.